Distinct dendritic morphology across the blades of the rodent dentate gyrus. Issue 7 (7th April 2016) - Gallitano, Amelia L.; Satvat, Elham; Gil, Mario; Marrone, Diano F.
ABSTRACT: The dentate gyrus (DG) is a hippocampal region that has long been characterized as a critical mediator of enduring memory formation and retrieval. As such, there is a wealth of studies investigating this area. Most of these studies have either treated the DG as a homogeneous structure, or examined differences in neurons along the septal‐temporal axis. Recent data, however, have indicated that a functional distinction exists between the suprapyramidal and infrapyramidal blades of the DG, with the former showing more robust responses during spatial tasks. To date, few anatomical studies have addressed this functional gradient in rats, and no study has done so in the mouse. To address this, we investigated dendritic morphology and spine density in hippocampal granule cells of rats and mice using the Golgi‐Cox technique. We find that granule cells from the suprapyramidal blade of the DG contain greater dendritic material in the region receiving spatial information from the medial perforant path. This provides a potential anatomical substrate for the asymmetric response of the DG to spatial input.Synapse 70:277–282, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using the Golgi‐Cox technique, the authors show morphological differences between the granule cells of the suprapyramidal blade (DGsp) and infrapyramidal blade (DGip) of the dentate gyrus. In both rats and mice, more dendritic material is observed in the region receiving medial perforant path input. This provides a potential anatomical substrate for the asymmetric activity in the DG in response to spatial input.